An Optimal Underwater Colour Image Enhancement Using CAUF-MCAHE Technique - Jaiswal, Ayushi; Upadhyay, Jayprakash (International Journal of Computer Sciences and Engineering, 2025)
Underwater imaging posts a challenge due to the degradation by the absorption, scattering and color distortion occurred during light propagation & in poor lighting conditions in water medium. Many different image filtering techniques are utilized to improve image quality effectively. Images which are captured under water are generally degraded due to the effects of absorption and scattering. For example, underwater images with low contrast decrease the accuracy rate of underwater object detection and marine biology recognition. To overcome those limitations, a systematic underwater image enhancement method, which includes a contrast enhancement algorithm, is proposed. In this paper, we proposed an image based pre- processing technique i.e. CAUF-MCAHE algorithm to enhance the quality of the underwater images. Experiments are performed with some underwater images and results are compared with different existing algorithm. For comparing the performance, MSE mean square error and PSNR peak signal to noise ratio is used as parameters.